Investigations of several surface-active properties of alkylimidazoline salts - Melnyk, Anatoliy; Malik, Serhii; Kramarev, Serhii; Матvieievа, Tetiana; Papchenko, Viktoriia (Eastern-European Journal of Enterprise Technologies, 2013)
Investigations of surface active properties of amidoimidazolines and its salts described in this article. Imidazolines have been synthetized from linseed oil and diethylenetriamine under conditions determined before. Investigations have been conducted for samples of imidazoline which were got during synthesis in determined times. Acetic and alkylsulfuric salts of obtained imidazoline and intermediate samples have been used as well. Anticorrosive ability of alkylsulfuric salt of alkylimidazolines was much better than acetic salt and unneutralized imidazoline. The worst anticorrosive ability was shown by acetic salt of imidazoline. Defensive effect of alkylsulfuric salt is more than 99 % and by this parameter salt could be compared with well-known corrosion inhibitors. Interfacial tension and ability to form emulsion have been investigated for unneutralized imidazoline and its salts as well. The best ability to form emulsion has been shown by acetic salt. Minimum interfacial tension was shown by acetic salt of imidazoline as well. In the same time maximum interfacial tension was determined for alkylsulfuric salt and the same salt have the worst ability to form emulsion.